The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/eji.201747442
|View full text |Cite
|
Sign up to set email alerts
|

Induced CNS expression of CXCL1 augments neurologic disease in a murine model of multiple sclerosis via enhanced neutrophil recruitment

Abstract: Increasing evidence points to an important role for neutrophils in participating in the pathogenesis of the human demyelinating disease MS and the animal model EAE. Therefore, a better understanding of the signals controlling migration of neutrophils as well as evaluating the role of these cells in demyelination is important to define cellular components that contribute to disease in MS patients. In this study, we examined the functional role of the chemokine CXCL1 in contributing to neuroinflammation and demy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 65 publications
(97 reference statements)
3
38
0
Order By: Relevance
“…Conversely, inducible overproduction of CXCL1 by astrocytes reduced EAE clinical disease, although it was unclear whether increased levels of CXCL1 directly affected oligodendrocyte biology or modulated immune cell recruitment into the CNS (65). We have recently shown that induced expression of CXCL1 resulted in increased demyelination mediated by neutrophils in both JHMV and EAE models of neurologic disease (18,19). In addition, previous work from our laboratories employing antibody-mediated targeting of CXCR2 shows that blocking signaling in JHMV-infected mice increases the severity of demyelination, arguing for a protective role for CXCR2 in a model of virus-induced demyelination, as previously discussed (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, inducible overproduction of CXCL1 by astrocytes reduced EAE clinical disease, although it was unclear whether increased levels of CXCL1 directly affected oligodendrocyte biology or modulated immune cell recruitment into the CNS (65). We have recently shown that induced expression of CXCL1 resulted in increased demyelination mediated by neutrophils in both JHMV and EAE models of neurologic disease (18,19). In addition, previous work from our laboratories employing antibody-mediated targeting of CXCR2 shows that blocking signaling in JHMV-infected mice increases the severity of demyelination, arguing for a protective role for CXCR2 in a model of virus-induced demyelination, as previously discussed (37).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR2 is a receptor for ELR-positive CXC chemokines, e.g., CXCL1 and CXCL2, and is expressed on polymorphonuclear neutrophils (PMN) as well as glia (12)(13)(14)(15)(16). CXCR2 signaling on neutrophils promotes demyelination in models of experimental autoimmune encephalomyelitis (EAE), cuprizone-induced demyelination, as well as virus-induced demyelination (8,(17)(18)(19). However, CXCR2 has additional roles that extend beyond influencing neutrophil activity, as it is expressed on immature oligodendrocyte progenitor cells (OPCs) as well as mature myelinating oligodendrocytes (20).…”
mentioning
confidence: 99%
“…EAE was initiated using a myosin oligodendrocyte protein (MOG)/Bordetella pertussis toxin (PT) method [15]. Briefly, mice were subcutaneously injected with 0.2 μmol of MOG peptide (MEVGWYRSPFSRVVHLYRNGK, synthesized at the University of Utah HSC Core) in complete Freund's adjuvant (CFA, Sigma, 2 mg/mL).…”
Section: Induction and Scoring Of Eaementioning
confidence: 99%
“…Spinal cords were isolated at defined time points and fixed overnight with 4% paraformaldehyde at 4°C. Sections were subsequently cryoprotected in 30% sucrose for 5-7 days, separated into 12 coronal sections and embedded in optimum cutting temperature (OCT) formulation (VWR, Radnor, PA, USA) [15,[19][20][21]. Coronal sections (8-μm thick) were cut, and sections were stained with luxol fast blue (LFB) in combination with hematoxylin and eosin (H&E).…”
Section: Histologymentioning
confidence: 99%
“…Production of IL-17 and CXCL1 has previously been shown to enhance recruitment of neutrophils to inflamed tissues and enhance their activity in certain disease contexts [45-50]. Neutrophil recruitment to the central nervous system however, has been shown to be detrimental in many cases [50-52]. With the increased mRNA levels of both IL-17 and CXCL1 seen in the brain after IL-10R blockade, we wanted to assess whether more neutrophils were recruited to the inflamed brain in this context.…”
Section: Resultsmentioning
confidence: 99%